Geology and Hydrogeology of Faults on Cape Breton Island, Nova Scotia, Canada: an overview - Baechler, Fred (Atlantic Geology, 2015)
Cape Breton Island provides a hydrogeological view into the roots of an ancient mountain range, now exhumed, glaciated, and tectonically inactive. It exhibits deep crustal faults and magma chambers associated with formation of the Appalachian mountain belt and the Maritimes Basin during the Paleozoic, as well as Mesozoic rifting relating to the opening of the Atlantic Ocean. Cenozoic exhumation brought these features near surface and into the active groundwater flow field where they were impacted by glaciation and fluctuating sea level. The faults have been important from a societal viewpoint in development of municipal groundwater supplies, controlling inflows to excavations, hydrocarbon exploration, quarry development, and geotechnical investigations. Conceptual models presented here outline fault control on groundwater flow based on seven case studies. Future research should focus on basin-bounding faults in support of managing their role in aquifer development and protection, mountain-front recharge, controlling large-magnitude springs, groundwater–stream interaction, and channel morphology. The hydrogeological importance of these faults has historically been underappreciated.